Analisis Pendapatan Usaha Tani Polikultur Rumput Laut, Bandeng dan Udang Windu di Desa Kedungpandan, Kecamatan Jabon, Kabupaten Sidoarjo - Anam, Anwarul Khafidhu; Noverma; Setiawan, Fajar (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Kedungpandan Village is a Jabon District, Sidoarjo Regency which has the potential of a large pond area and the potential for polyculture farming. There is a polyculture of seaweed, milkfish and tiger shrimp farming in Kedungpandan Village. The research was conducted in Kedungpandan Village, Jabon District, Sidoarjo Regency. The purpose of this study was to determine how much income and factors that influence income and whether or not polyculture farming is feasible in Kedungpandan Village. Primary data was collected by means of interviews, questionnaires and observations, while secondary data were obtained from BPS Jabon District and data from DKP Sidoarjo Regency. The results showed that the average income of Rp.73,700,219 per year, with an average cost of Rp. 136,313.960 per year and the average revenue is Rp. 210,014,179 per year. The factors that partially influence income on work experience, selling price, and production have a positive and significant effect on income while the capital variable is not significant then, simultaneously on the variables of capital, work experience, selling price and production have a significant effect on income. In the feasibility of polyculture farming has an NPV value of Rp. 143.871.694,- R/C 1.54 B/C 3.56 and PP 10.8.